Problematic Internet Use: The Influence of Self-Esteem, Emotion Regulation, and Social Support in University Students - Nurul Astri; Gazi Saloom; Valendra Granitha Shandika Puri; Akhmad Baidun (Universitas Islam Negeri Madura, 2026)
Problematic internet use has increasingly become a concern alongside the rapid advancement of digital technology. This study aims to examine the influence of self-esteem, emotion regulation, and social support as independent variables on problematic internet use. A quantitative approach was employed involving 254 university students in the Greater Jakarta area selected through non-probability sampling. Data were collected using the Generalized Problematic Internet Use Scale 2 by Caplan (2010), Self-Liking/Self-Competence Scale by Tafarodi & Swann (2001), Emotion Regulation Questionnaire by Gross & John (2003), and Multidimensional Scale of Perceived Social Support by Zimet et al. (1988). The results show that self-esteem, emotion regulation, and social support simultaneously have a significant effect on problematic internet use, contributing 36,9%. At the dimensional level, self-liking negatively predicts problematic internet use, while self-competence and expressive suppression show significant positive effects. Cognitive reappraisal and all dimensions of social support do not show significant effects. These findings highlight the importance of internal psychological factors, such as self-esteem and emotion regulation, in explaining problematic internet use.